2017
DOI: 10.1002/ccd.27153
|View full text |Cite
|
Sign up to set email alerts
|

Fighting fungus with a laser and a hose: Management of a giant Candida albicans implantable cardioverter‐defibrillator lead vegetation with simultaneous AngioVac aspiration and laser sheath lead extraction

Abstract: Infections involving internal cardiac devices can be very challenging to treat, and almost universally require complete device extraction for successful management. Of the pathogens that cause device-related endocarditis, fungi such as Candida albicans are notoriously difficult to manage because of their propensity to produce large vegetations and the need for long-term treatment with potentially toxic medications. Furthermore, individuals who develop fungal, device-associated endocarditis are typically among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…Studies have shown it to be an effective method of percutaneous removal of thrombi and right-sided vegetations [2][3][4]. Reports have also shown it to be useful in management of vegetations associated with pacemaker and defibrillator leads [5][6]. However, as in the patient presented here, cases of incomplete extraction and distal embolization have been reported.…”
Section: Discussionmentioning
confidence: 81%
“…Studies have shown it to be an effective method of percutaneous removal of thrombi and right-sided vegetations [2][3][4]. Reports have also shown it to be useful in management of vegetations associated with pacemaker and defibrillator leads [5][6]. However, as in the patient presented here, cases of incomplete extraction and distal embolization have been reported.…”
Section: Discussionmentioning
confidence: 81%
“…Out of 53 retrieved searched articles, 42 met our inclusion criteria. The PRISMA flowchart is shown in Figure S1.…”
Section: Resultsmentioning
confidence: 99%
“…With regard to the fungal aetiology, the large vegetations of the Eustachian valve and the apex of the right ventricle, early surgery which was refused by the patient would have been indicated [34]. Here, alternatively to an open surgery, minimal invasive extraction of large CIED-IE and large right-sided IE vegetations with an AngioVac system [[41], [42], [43], [44], [45], [46], [47], [48], [49]] or with a wire snare [50] might prove beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…for 2 months2 months follow up without relapse[82]70/FPrior day hospital for 1 week due to urinary tract infection with septic shock (Vancomycin 1 day, Piperacillin/Tazobactam 3 days, followed by Ciprofloxacine p.o. ), DM, CKD, CHF, survived SCD13 months Single lead ICDNausea, vomiting, fatigue, feverBC/UC: C. glabrata TOE: Multiple vegetations on ICD, AV vegetation, new tricuspid regurgitationHepatotoxicityCaspofungin 70 mg/d for 2 daysCaspofungin 100 mg/d and Flucytosine 37.5 mg b.i.b.Micafungin 150 mg/d instead of Caspofungin due to hepatotoxicityDeceased on day 31[83]65/FHypertension, CKD, haemodialysis, DCM and ICM, SCD due to VF, 1 month before CIED-IE septic shock due to perforated diverticular disease12 months ICDSeptic shockBC: C. albicans TOE: 23 mm vegetation on ICD electrodeSeptic shock, bilateral pulmonary septic embolismLiposomal Amphotericin B (5 mg/kg/d)ICD explantationCaspofungin added (70 mg day 1, 50 mg/d)Reimplantation after 4 weeks (>72 h no fever)6 more weeks of liposomal Amphotericin B/CaspofunginNo follow up[41]25/FNICM, NYHA IV, LV-EF 10%, obesity, hypertension, DM, DVT, pulmonary embolism, palliative inotrope therapy via Hickmann catheter: multiple bloodstream infections32 months Single lead ICDNot definedBC: C. albicans TOE: 61,3 × 16,5 mm in the RA from SVC +21 × 16 mm RA part of RV electrodeSeptic pulmonary embolismsMicafunginAngioVac extraction s-ICD implantation 10 days laterLong-term oral Fluconazole8 months follow up without relapseBauer et al, 201964/MSurvived SCD due to VF, single lead ICD 14 months earlier, replacement due to loss of sensing 6 months earlier, CAD, paroxysmal AF, CKD14 months Single lead ICD6 months Lead revisionAsymptomaticICD and lead: C. tropicalis TTE/TOE: 40 × 17 mm on EV, 22 × 15 mm in RVPulmonary embolismPercutaneous explantationLiposomal Amphotericin B 5 mg/kg/d for 28 days and 3 mg/kg/d due to nephrotoxicity for 28 daysFlucytosine 25 mg/kg q.i.d. for 56 daysLifeVest Bridging and s-ICD Implantation 1 month after antifungal therapy14 months Follow up without relapseAF – Atrial fibrillation; CAD – Coronary artery disease; CHF – congestive heart failure; CKD – Chronic kidney disease; CVA – cerebrovascular accident; DM – Diabetes mellitu...…”
Section: Discussionmentioning
confidence: 99%